Early Onset Primary Hyperparathyroidism Associated with a Novel Germline Mutation in CDKN1B - Marianne S. Elston; Goswin Y. Meyer-Rochow; Michael Dray; Michael Swarbrick; John V. Conaglen (Case Reports in Endocrinology)
Individuals presenting with primary hyperparathyroidism (PHPT) at a young age commonly have an underlying germline gene mutation in one of the following genes: MEN1, CASR, or CDC73. A small number of families with primary hyperparathyroidism have been identified with germline mutations in CDKN1B and those patients with primary hyperparathyroidism have almost exclusively been women who present in middle age suggesting that the age of onset of PHPT in MEN4 may be later than that of MEN1. We present a case of apparently sporadic PHPT presenting in adolescence with single gland disease associated with a novel CDKN1B germline mutation (heterozygote for a missense mutation in exon 1 of the CDKN1B gene (c.378G>C) (p.E126D)). The implication from this case is that CDKN1B germline mutations may be associated with PHPT at an earlier age than previously thought.